Reimagining Indigenous Knowledge: An Epistemological Critique against the Neo-colonial Violence in the Selected African Novels - Quratulan; Anjum, Arsalan; Ahmed, Ayesha (Annals of Human and Social Sciences, 2024)
The objective of this study is to examine how indigenous knowledge can prove to be an effective source of liberating people from neo-colonial domination. While doing a textual analysis of the novels, Half of a Yellow Sun by Chimamanda Ngozi Adichie (2006) and The Beautyful Ones Are Not Yet Born by Ayi Kwei Armah (1968), the research dilates upon the ideas of Edward W. Said’s (1978) Orientalism and Frantz Fanon’s (1963) The Wretched of the Earth, to celebrate indigenous knowledge formation practices. The methodological assumptions of this study help to describe the interaction of knowledge with power and subject formation in the context of colonial discourses. As a result, this work posits that the idea of knowledge can be used to accomplish the task of deconstructing coloniality and its domination schema. The study recommends that the novels promote indigenous episteme to impart agency and voice to the oppressed segments of society.